The correlation between the properties and the type of reinforcement in Al-matrix powder-metallurgy composites - Vukčević, Mira (Materiali in tehnologije, 2001)
Al-SiC particles (Al-SiC$_{p}$) composites were fabricated by the admixture method using an Al-coated reinforcement and atomised matrix powder. The microstructure of the samples in the hot-pressed condition with the homogeneously dispersed reinforcement was monitored. The use of a coated reinforcement to make composites by powder metallurgy (PM) methods was found to yield superior mechanical properties than the use of a mixture of reinforcement and matrix powder. The coated-reinforcement sample had lower porosity, increased hardness and a higher compressive yield strength. The coating diminished direct reinforcement-reinforcement contact and promoted sintering with a resulting low porosity.
Keywords: metalurgija prahov; kompoziti; aluminij; aluminum; ojačitev; lastnosti